EAF smelting trials of briquettes at Avesta works of Outokumpu Stainless Steel AB for recycling oily mill scale sludge from stainless steel production - Yang, Qixing; Holmberg, Nils; Björkman, Bo (Luleå tekniska universitet, Industriell miljö- och processteknik, 2008)
The production EAF of Avesta Works, Outokumpu Stainless AB, has been used to perform smelting reduction trials of briquettes consisting of oily mill scale sludge, carbon and other wastes. The trials were among several important activities in studies on waste recycling by EAF smelting carried out jointly by Avesta Works and MiMeR, the Minerals and Metals Recycling Research Centre, at Luleå University of Technology. A total of 7 briquette smelting trials were performed. The heats were processed smoothly smelting 3 tonnes of briquettes or 3,4% of the weight for metal charges. Quantities of FeSi powder and O2 gas injected and electric energy supplied were increased while the briquette weight was increased to 6 tonnes. No impacts were found on analyses of the crude stainless steel tapped from the EAF during the trials. Results of the briquette smelting have been evaluated by referring to the data from the reference heats and results from early laboratory tests. The recovery of Cr, Ni and Fe elements from the briquettes was nearly complete and was found to occur mainly through carbon reduction. Positive effects of briquette smelting on protecting metallic charges against gaseous oxidation have also been identified. This protection was through CO gas, generated from solid state C-O reaction in the briquettes, reacting with oxygen in the intruding air. The protection reduced losses of Cr, Ni and Fe elements from metallic charges to the slag. The slag weights were not increased in three trials as compared with the reference heats. There were moderate increases in the slag weights in four trial heats. The increases were, nevertheless, lower by 52-69% than the slag weights generated by a Si-reduction of the briquette oxides. By smelting 6-tonnes of briquettes in the trials, reliable information and results on C-O reactions in the briquettes for recovery of metal elements in the production EAF were obtained. After the trials, carbon-waste briquettes amounting to 1-3 tonnes were smelted very smoothly in many of the EAF heats ...